The relationship between place and hallmark event; Malaysian cultural context / Musaddiq Khalil...[et.al] - Khalil, Musaddiq; Zainol, Amer Shakir; Dasuki, Shaliza; Marziana, Liza; Idris, Khazilah; Radzi, Fazlina (2016)
The tourism industry has been one of the major key-economic growths in Malaysia. Exploration of different types of events has changed the sector drastically in achieving the high impact factor. Hallmark Event has been one of the best solutions not only to create bigger crowds but to also promote and help the socio-culture around a selected area. This study attempts to enrich the previous semantic-tangle on hallmark event, thus broaden the gap of studies on hallmark event, specifically in Malaysia. The variables chosen to represent the semantic-tangle are loci/space, people/social, event/experience, and hallmark cultural impact. Using a fully quantitative method of research with a correlational research design, this study ought to prove the positive relationship between the variables, thus strengthening the previous gap done by previous researchers which would be applied specifically at Malaysia. Using convenience sampling of 100 visitors on the MAP Festival in 2013, this research managed to generate the descriptive statistic, reliability, validity, and the direct effect of each variables using Pearson Correlation. The results measured were strong relationship showing at least 0.60 positive, 2 tail significant relation between the variables loci/space, people/social, event/experience, and cultural impact of the hallmark event chosen. In gaining the high impact factor on a certain hallmark event in Malaysia, it is highly recommended that authorities would put into considerations of these loci, social, and event factor in determining a promising site specifically in Malaysia.